Enhancing Web Performance for E-learning Platform using Content Delivery Network (CDN) and Varnish Cache - Utomo, Muhammad Nur Yasir; Tungadi, Eddy; Khartika, Widya (Universitas Bina Darma, 2025)
Along with the development of technology, the web has become a very popular platform for providing information services and digital content, especially in education sector. The popularity of web services such as e-learning is directly proportional to the increasing number of users. The increase in the number of users is often a problem because it can lead to decreased web performance and potential downtime. To overcome this problem, this study proposes Content Delivery Network (CDN) and Varnish Cache as solutions. Web performance evaluation was carried out in a campus internal network using Apache JMeter with a load of 1,000 users. Based on the evaluation, there was a 175.5% increase in throughput, from 51.9 to 142.9 requests per second. In terms of response time, it improved by 54.3%, decreasing from 16,476 ms to 7,526 ms. Additionally, latency was reduced by 82.4%, from 3,555.8 ms to 624.8 ms. The error rate also decreased from 31.4% to 17.2%. These results indicate that CDN implementation can effectively improve web server performance and provide an optimal user experience, especially under high load conditions.